Vancomycin Utilization Evaluation in a Tertiary Teaching Hospital in Mashhad, Iran - Mohaddeseh Sadat Ayubi; Sepideh Elyasi; Mahdi Jannati; Naser Vahdati-Mashhadian; Mohammad Reza Saberi; Hamid Reza Naderi; Amir Hooshang Mohammadpour (Research Center for Rational Use of Drugs (RCRUD), 2018)
Introduction: Inappropriate use of antibiotics in health care systems can lead to bacterial resistance, nosocomial infections and increased hospital costs. So, evaluation programs for these medications are needed. This study evaluates the pattern of vancomycin utilization in Imam Reza hospital, Mashhad, Iran.  Methods: At first, according to drug information sources a check list was designed for appropriate indication and dosing of vancomycin. One hundred patients were selected randomly from different wards of hospital during a 6 months period and their data were collected in predesigned check list. Then, data were evaluated according to prepared checklist. Results: In this study, 100 patients (48 female and 52 male) were evaluated. Empiric therapy in 20% of patients was not initiated appropriately based on prepared checklist. Empiric regimen was changed in 10 patients based on culture results and in 28 patients regarding clinical response. Prescribed doses were according to the guideline in only 31% of patients. Duration of treatment were inappropriate in 35 patients. Vancomycin induced nephrotoxicity occurred in 7 patients and red man syndrome in 1 patient. Administration procedure was correct in all patients.  Conclusion: According to the results, lots of error occurred in vancomycin administration and dosing in our center. It is necessary to develop localized guideline for vancomycin utilization in this hospital to prevent unwanted adverse reactions and antimicrobial resistance and also reduce treatment cost.